An Evaluation of Niche Separation in the Terrestrial Primate Fauna of Plio-Pleistocene South Africa Using Biogeochemical Data - Ethan Fulwood (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
Human evolution in the Plio-Pleistocene occurred in the context of a community of large-bodied terrestrial primates which may have shaped aspects of australopithecine ecology. Ecological theory would predict a degree of niche separation between these closely related sympatric species. Here, data from published biogeochemical paleodiet studies are used to test this hypothesis. The use of biogeochemistry in approximating niche width has been suggested on the basis of its reflection of an average of the total diet of an organism and its linear comparability between observations (Bearhop et al. 2004). Data on two measures, δ13C, which indicates the photosynthetic pathway of the dominant plants in the trophic chain of an organism, and Sr:Ba ratios, which can indicate trophic level, were analyzed using ANOVA and Tukey’s test for significant difference in 8 Plio-Pleistocene primate species and groups of C3 browsers and C4 grazers. In δ13C, three groups were distinguished: grazers and Theropithecus; Australopithecus, Parapapio, Papio, and Cercopithecoides; and Papio, Cercopithecoides, and the browsers. In Ba:Sr, two groups were distinguished: A. africanus, A. robustus, and Papio; and A. robustus, Papio, and Parapapio. Due to the significant degree of overlap between genera in both metrics, with the exception of Theropithecus, there is a lack of support for a strong degree of niche separation in this sample. It is possible that these taxa were able to coexist by adopting seasonally or spatially variable feeding behaviors, or their diets were less similar than appears from these biogeochemical indicators alone.
Keywords: Evolution; Plio-Pleistocene; Fauna; South Africa